Reflecting on Metacognitive Strategies in F. L. Teaching and Learning - Ojeda Álvarez, Adriana (Universidad Pedagógica y Tecnológica de Colombia, 2012)
The present reflection has been written in order to compile the most relevant features that set up metacognitive strategies in connection with second language teaching and learning. The review of literature offers a wide field of practical and effective actions to be included during the classes in order to strengthen metacognitive skills and empower second language learners. It is important to emphasize the representative role of teaching instruction in establishing conditions for the generation of awareness in students as a result of an accurate process of thinking. Finally some points for discussion are presented, which provide rhetorical questions to be answered during an ongoing process of reflection and teaching experience.